The Effect of Emotional Valence and Arousal on Visuo-Spatial Working Memory: Incidental Emotional Learning and Memory for Object-Location - Costanzi, Marco; Cianfanelli, Beatrice; Saraulli, Daniele; Lasaponara, Stefano; Doricchi, Fabrizio; Cestari, Vincenzo; Rossi-Arnaud, Clelia (Frontiers in Psychology, 2019)
Remembering places in which emotional events occur is essential for individual’s survival. However, the mechanisms through which emotions modulate information processing in working memory, especially in the visuo-spatial domain, is little understood and controversial. The present research was aimed at investigating the effect of incidentally learned emotional stimuli on visuo-spatial working memory performance by using a modified version of the object-location task. Eight black rectangles appeared simultaneously on a computer screen; this was immediately followed by the sequential presentation of eight pictures (selected from IAPS) superimposed onto each rectangle. Pictures were selected considering the two main dimensions of emotions: valence and arousal. Immediately after presentation, participants had to relocate the rectangles in the original position as accurately as possible. In the first experiment arousal and valence were manipulated either as between-subject (Experiment 1A) or as within-subject factors (Experiment 1B and 1C). Results showed that negative pictures enhanced memory for object location only when they were presented with neutral ones within the same encoding trial. This enhancing effect of emotion on memory for object location was replicated also with positive pictures. In Experiment 2 the arousal level of negative pictures was manipulated between-subjects (high vs. low) while maintaining valence as a within-subject factor (negative vs. neutral). Objects associated with negative pictures were better relocated, independently of arousal. In Experiment 3 the role of emotional valence was further ascertained by manipulating valence as a within-subject factor (neutral vs. negative in Experiment 3A; neutral vs. positive in Experiment 3B) and maintaining similar levels of arousal among pictures. A significant effect of valence on memory for location was observed in both experiments. Finally, in Experiment 4, when positive and negative pictures were encoded in the same trial, no significant effect of valence on memory for object location was observed. Taken together results suggest that emotions enhance spatial memory performance when neutral and emotional stimuli compete with one another for access into the working memory system. In this competitive mechanism, an interplay between valence and arousal seems to be at work.